Digital finance and Chinese corporate labor investment efficiency: The perspective of financing constraints and human capital structure - Yang, Jing; Jiang, Yalin; Chen, Hongan; Gan, Shengdao (Frontiers in Psychology, 2022)
As the aging population problem intensifies, many emerging economies are caught in labor shortage and rising labor costs, thus improving the corporate labor investment efficiency is crucial for these countries. In this context, we take China as an example to explore the influence of the current booming digital finance on corporate labor investment efficiency. This paper, which enriches the existing literature, is one of the few studies that explores the link between macroeconomic policies and firms' labor investment efficiency. Our research adopts the baseline methodology of ordinary least squares (OLS) regression, and the data comprise 23,503 observations for Chinese A-share listed businesses from 2011 to 2020. In addition, we use fixed effects regression, instrumental variables method and substitution of independent variables to deal with endogeneity and test the robustness. The outcomes suggest that digital finance may significantly increase corporate labor investment efficiency. Further results from the path mechanism study suggest that digital finance could alleviate financing constraints and optimize human capital structure, both of which have a favorable effect on the labor investment efficiency. Last but not least, the heterogeneity results imply that digital finance can more effectively encourage labor investment efficiency of firms in economically underdeveloped regions and of private nature. The study recommends that emerging economies should pay attention to strengthening regulation to avoid financial risks while vigorously promoting digital finance. In addition, enhancing the level of human capital and optimizing human capital allocation are also essential.